Intervensi Pemberian Terapi Dan Posisi Semi Fowler Pada Anak Dengan Bronkopneumonia - Yulia Rahmawati; Muadi; Raeisya Azrilliyani; Julia Afriani; Vivy Zakiyah (MEJORA Medical Journal Awatara, 2024)
The basic need for oxygenation is one of the most vital basic needs in human life. This is related to the cellular metabolic process, where this process requires oxygen in the body. The impact that occurs if the lack of oxygen in the body is not immediately resolved can cause a lack of oxygen in the body's cells. Body cells that lack oxygen will have difficulty concentrating because metabolism is disrupted due to a lack of oxygen supply in the blood. This case study aims to explain nursing care for patients with a diagnosis of Bronchopneumonia medicine using oxygenation therapy interventions, nebulizer inhalation therapy, and semi-fowler position or head up 30o. This research uses a qualitative approach with case studies as the main method, using observation sheets, interviews, and documentation studies. The subject of this research was one patient, An. K patient with bronchopneumonia at Sumber Kasih Hospital, Cirebon City. The results of the case study showed clinical success that the nursing problem of ineffective airway clearance and ineffective breathing patterns was resolved by increasing airway clearance, improving breathing patterns, and increasing oxygen saturation.